The Effect of Beta Adrenergic Blockade upon Exercise-Induced Changes in Blood Coagulation and Fibrinolysis - Britton, B.J; Wood, W.G; Smith, Muriel; Hawkey, Christine; Irving, M.H (Thrombosis and Haemostasis, 1976)
Exercise stress is known to stimulate blood coagulation and fibrinolysis possibly as a result of sympatho-adrenal stimulation of the beta adrenergic receptor. In order to test this hypothesis five men exercised on four separate occasions with and without prior beta adrenergic blockade with oxprenolol, propranolol and pindolol. The increase in plasma adrenaline and noradrenaline concentration was much greater during exercise under beta blockade but activation of fibrinolysis was enhanced as well. Factor VIII levels did not change significantly during any of the experiments. These results suggest that the activation of fibrinolysis by exercise is not mediated by the beta adrenergic receptor. The influence of beta adrenergic blockade on the change in factor VTII with exercise was inconclusive.